An efficient approach for 3-haloquinoline synthesis: PhI(OAc)2-mediated A3-X type tandem annulation of amine, aldehyde, alkyne and halide salt. (6th July 2022) - Lu, Hongbin; Qiu, Yu-Chen; Zhao, Qin; Tang, Rui; Chen, Tingting; Hu, Lanping; Wu, Zheng-Guang
Graphical abstract: A PhI(OAc)2 -mediated four-component tandem annulation with basic modules of amine, aldehyde, alkyne and halide salt for concise and efficient synthesis of functionalized 3-haloquinolines has been established. This strategy merging A3-coupling and redox reaction of halide salt, namely A3-X type tandem reaction, is step economic, functional groups flexible, and potentially applicable to complex molecules. Abstract: Utilizing simple precursors for the exquisite construction of molecules with diversity and complexity is urgent. Herein, a novel A3-X type reaction for functionalized 3-haloquinolines has been developed by PhI(OAc)2 -mediated four-component tandem addition/cyclization/oxidation/aromatization process with simple aromatic amine, aldehyde, alkyne and halide salt. Broad functional group tolerance, very mild condition, easy for further transformation illustrate the concision, high efficiency and practicability of this A3-X type reaction.